Генерал и его армия: роман / Г. Н. Владимов - Владимов Г. Н. (Отечественная проза, 2004)
Экземпляры: аб. (2005) / Инвентарный номер: 48535 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 57 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6